-(x+5)=-17+5x

Simple and best practice solution for -(x+5)=-17+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+5)=-17+5x equation:


Simplifying
-1(x + 5) = -17 + 5x

Reorder the terms:
-1(5 + x) = -17 + 5x
(5 * -1 + x * -1) = -17 + 5x
(-5 + -1x) = -17 + 5x

Solving
-5 + -1x = -17 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-5 + -1x + -5x = -17 + 5x + -5x

Combine like terms: -1x + -5x = -6x
-5 + -6x = -17 + 5x + -5x

Combine like terms: 5x + -5x = 0
-5 + -6x = -17 + 0
-5 + -6x = -17

Add '5' to each side of the equation.
-5 + 5 + -6x = -17 + 5

Combine like terms: -5 + 5 = 0
0 + -6x = -17 + 5
-6x = -17 + 5

Combine like terms: -17 + 5 = -12
-6x = -12

Divide each side by '-6'.
x = 2

Simplifying
x = 2

See similar equations:

| 15-2x-2=10x+3+2 | | 102.74=-1.4-3.37(-3.5n-2.85) | | x+7+6x=91 | | 7x^2-24x-55= | | 1/3x=3x-4/5 | | -30+3y=90 | | 7[6-9(x-1)]+4[(5x+2)-3]=11x-341 | | 12y+38=10 | | (1-4x)/e^4x=0 | | 7+4x-x=16 | | -n-3.16(3.83n+1.6)=-94.17 | | 5z=4y | | -2(5y-5)-y=-4(y-4) | | x-7y=15-x | | -89.08=-4(4.87x+.33) | | 12=-n-2n | | -24.7938=9.7+x | | 6(2x-7)(3x+7)=0 | | 44=3y+11 | | 10.6375=5.75(a+1.2) | | 7y-8=3y-12 | | 450/8= | | -2+7x=2x+8 | | (-12)=w/4 | | x^2-4z=0 | | 18X-5Y-9X+Y= | | x^4-4x^3-20x^2-80x+208=0 | | M=D+Drt | | n/(-2)=-15 | | 7-0.2x=54 | | -9-5x=-1+3x | | 3x=4+-1y |

Equations solver categories